Biotransformation of ethyl p-methoxycinnamate from Kaempferia galanga L. using Aspergillus niger - Mohd Hasali, Nor Hazwani; Omar, Muhammad Nor; Zuberdi, Ahmad Muzammil; Alfarra, Helmi Yousif (International Network for Natural Sciences, 2013)
Studies were carried out on the extraction of the rhizome of Kaempferia galanga L. using steam distillation and supercritical fluid extraction (SFE). After purification, the major compound of the K. galanga L. extract, ethyl methoxycinnamate (EPMC) was identified by NMR and MS spectrometry. Biotransformation of EPMC using Aspergillus niger afforded ethyl p-hydroxycinnamate in 24% yield.